2013
DOI: 10.1002/ccd.
|View full text |Cite
|
Sign up to set email alerts
|

Early clinical experience with a modified amplatzer ductal occluder for transcatheter arterial duct occlusion in infants and small children

Abstract: The new amplatzer ductal occluder II AS achieves excellent ductal closure rates through low profile delivery systems in small infants and children with variable ductal anatomy. © 2012 Wiley Periodicals, Inc. © 147.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…However, the ADO I requires a larger sheath, is not suitable for use in tubular, type C PDAs, and can only be applied in an antegrade manner, all of which restrict the use of the ADO I in smaller patients . As reported in the studies that compared the use of Amplatzer duct occluders (ADO I, II, and II AS) in children who weighed less than 10 kg and showed that the ADO II AS is suitable for use in small children and premature infants because it can be used both in a retrograde and antegrade manner, it can embed the retention discs in PDA, it requires a 4F sheath, and it can be used in type C ducts . Free coils and Cook detachable coils can also be used in premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ADO I requires a larger sheath, is not suitable for use in tubular, type C PDAs, and can only be applied in an antegrade manner, all of which restrict the use of the ADO I in smaller patients . As reported in the studies that compared the use of Amplatzer duct occluders (ADO I, II, and II AS) in children who weighed less than 10 kg and showed that the ADO II AS is suitable for use in small children and premature infants because it can be used both in a retrograde and antegrade manner, it can embed the retention discs in PDA, it requires a 4F sheath, and it can be used in type C ducts . Free coils and Cook detachable coils can also be used in premature infants.…”
Section: Discussionmentioning
confidence: 99%
“…The reported initial experiences with a modified Amplatzer PDA closure device named ADO II Additional Sizes (ADO II‐AS) has been encouraging with no reported LPA obstruction and particularly useful in small infants and even in preterm babies . The ADOII‐AS device is a three‐lobed cylindrical device with lateral discs just 1–1.5 mm larger than the central body making its shape closer to an AVP II than an ADO II.…”
Section: Discussionmentioning
confidence: 99%
“…The ADO II AS device has similar construction and design to ADO II; however, the two symmetrical retention discs have been modified to only 1–1.5 mm larger in diameter than the waist in an attempt to minimize the potential for device related LPA stenosis or coarctation. We used the device in six patients which have previously been reported in a multicenter study . These patients were smaller with a median weight of 6.25 kg (range: 4.36–9.4 kg) and median age of 8.4 months (range 4.1–18.7 months).…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical experiences with the ADO II have been reported with high success rates in a variety of ductal morphologies . More recently, another ADO design has been introduced, Amplatzer duct occluder II Additional Sizes (ADO II AS) with even smaller retention discs and lower profile delivery system . This article reports our long‐term clinical experience with the ADO II in a variety of ductal sizes and morphology in children over a period of five years, with emphasis on long‐term occlusion rates and complications.…”
Section: Introductionmentioning
confidence: 99%